KEPUASAN PELANGGAN MEMEDIASI HARGA DAN PROMOSI TERHADAP LOYALITAS PELANGGAN - Dwi Gemina; Mia Maulani Agustin; Samsuri, Samsuri (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Competition in the business world in the service sector today requires companies to be more careful in carrying out management and marketing strategies. The strategy that can be done to maintain the continuity of its business is to provide satisfaction to customers in order to create customer loyalty. This study aims to determine the direct effect, indirect effect and total effect of price and promotion on customer loyalty through customer satisfaction. The sample in this study amounted to 100 respondents conducted by purposive sampling. The data used in this study is ordinal data which is converted into interval-scale mentrik data with Method Of Successive Interval (MSI) through the Microsoft office Excel program. Data analysis using descriptive analysis, verification analysis, path analysis and Sobel Test analysis for intervening variables through the IBM SPSS Version 25.00 program. The results of this study indicate that there is a direct and positive effect of price and promotion on customer satisfaction. There is a direct and positive effect of price and promotion on customer loyalty. There is a direct and positive effect of customer satisfaction on customer loyalty. There is an indirect and positive effect of price and promotion on customer loyalty through customer satisfaction